(untitled) (Lex localis - Journal of Local Self-Government, 2025)
The relationship between teachers and students is the relationship between teachers and students. It is a special expression of the relationship between "people" in educational activities. It is both an ordinary and special interpersonal relationship. Among all the relationships in school education and teaching, it is the most basic, the most common, the most core and the most important. The relationship between teachers and students affects the organization of teaching activities, the quality and level of education, and the individual development of teachers and students.As an important carrier of campus culture, the teacher-student relationship is the most basic and important interpersonal relationship in college education and teaching activities. It not only directly affects the effect of education and teaching, but also has a profound impact on students’ mental health, personality development and future career planning. The harmonious relationship between teachers and students can promote effective communication and interaction between teachers and students, so that teachers can better understand the needs and confusion of students, so as to provide more targeted guidance and help, which is of great significance to enhance students’ learning motivation and self-confidence, and promote students’ comprehensive development.